Potentially preventable trauma deaths: A retrospective review. Issue 5 (May 2019) - Beck, Ben; Smith, Karen; Mercier, Eric; Bernard, Stephen; Jones, Colin; Meadley, Ben; Clair, Toby St; Jennings, Paul A.; Nehme, Ziad; Burke, Michael; Bassed, Richard; Fitzgerald, Mark; et al.
Highlights: An expert panel review methodology was used to identify the rate of preventable and potentially preventable trauma deaths. Potentially preventable or preventable deaths represented 7% of cases that had attempted resuscitation from paramedics. Identifying situations where the system of care was considered suboptimal provides opportunities to improve trauma systems. Abstract: Background: Reviewing prehospital trauma deaths provides an opportunity to identify system improvements that may reduce trauma mortality. The objective of this study was to identify the number and rate of potentially preventable trauma deaths through expert panel reviews of prehospital and early in-hospital trauma deaths. Methods: We conducted a retrospective review of prehospital and early in-hospital (<24 h) trauma deaths following a traumatic out-of-hospital cardiac arrest that were attended by Ambulance Victoria (AV) in the state of Victoria, Australia, between 2008 and 2014. Expert panels were used to review cases that had resuscitation attempted by paramedics and underwent a full autopsy. Patients with a mechanism of hanging, drowning or those with anatomical injuries deemed to be unsurvivable were excluded. Results: Of the 1183 cases that underwent full autopsies, resuscitation was attempted by paramedics in 336 (28%) cases. Of these, 113 cases (34%) were deemed to have potentially survivable injuries and underwent expert panel review. There were 90 (80%) deaths that were not preventable, 19 (17%) potentially preventable deaths and 4 (3%) preventable deaths. Potentially preventable or preventable deaths represented 20% of those cases that underwent review and 7% of cases that had attempted resuscitation. Conclusions: The number of potentially preventable or preventable trauma deaths in the pre-hospital and early in-hospital resuscitation phase was low. Specific circumstances were identified in which the trauma system could be further improved.